Perancangan User Interface Sistem Informasi Administrasi Warga Tingkat RT berbasis Web menggunakan Metode Human-Centered Design - Olga Oktavia Rahayu; Buce Trias Hanggara; Bondan Sapta Prakoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
RT 001 is one of the RTs in RW 013, Buliang Village, Batam City. The problem felt by RT 001 is the repetitive process of recording citizen data and the use of paper media that takes time for RT administrators to obtain complete and accurate citizen data. Based on this, this research seeks to create a user interface design for a web-based citizen administration information system to assist RT administrators in recording citizen data, which allows residents to update data independently and stored in the system so that RT administrators can access it through the system. This design produces a high-fidelity prototype that is divided into two user groups, namely RT administrators and residents using the Human-Centered Design (HCD) method as the design method. Testing was conducted using Usability Testing and System Usability Scale (SUS) to measure aspects of user satisfaction. The effectiveness aspect in the user group of RT administrators and residents received an above-average score of 100%. The efficiency aspect in the RT management user group received a result of 0.085 goals/sec and in the citizen user group received a result of 0.0922 goals/sec. The user satisfaction aspect in the RT management user group received a score of 79.5 and in the citizen user group received a score of 77 so that both received a Good predicate in the adjective category.